Effective Writing Skills to Meet Academic Needs and Workplace Requirements - Allaberdieva Gulshoda Bakhtiyarovna (International Journal on Integrated Education, 2022)
This article is about students need effective writing skills to meet their academic needs and workplace requirements. Students should improve their writing skills, for which teachers have to motivate them to have good writing skills, by providing instruction in writing processes and rules of writing, such as grammar rules and writing practice. They should develop the writing skills for their multiple benefits and success in life. The process of writing is to teach students how to write with coherence, an appropriate grammar structure and an acceptable spelling.